Pengaruh Pemberian Remunerasi Terhadap Kinerja Anggota Polri Pada Satuan Intelkam Polresta Barelang - Dwi Nurhuda; Didi Sundiman; Fatia Fatimah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Performance allowance or also known as salary is an award or remuneration given by the company for the company's goals. In this case, the performance allowance means that the organization or institution should not ignore its existence in the company organization. The questions explored in this study are as subtle as the major influences that give performance or gratuities to the performance of 41 members of the Barelang Police. The purpose of this study is to use data analysis methods (namely descriptive analysis, simple linear regression analysis and data normality test using SPSS) to see whether it affects performance. The results showed that the performance permit variable (X1) has a significance value (Sig.) Of 0.001 in the Coefficientsa table, the α (significance) value of 0.05 means 0.001 <0.05 or has a significant effect, and the t test shows 3.520> t table (2.000 ).